The Heritage of Emancipation: Collecting the (Invisible) Everyday - Milena Jokanović; Ivan Đorđević; Marija Đorđević (Etnoantropološki Problemi)
Participatory heritage mapping is one of the possible methods for valorizing emancipation practices as cultural heritage. Through the citizen science research project "HEROINES: Heritage of Emancipation - Empowering Roma Women through the Construction of Solidarity Networks", conducted by researchers from the Institute of Etnography, SASA, and the Faculty of Philosophy – University of Belgrade, in cooperation with Roma activists from Belgrade, Kostolac, and Pirot, the heritage of women's activism was defined as a distinct form of everyday life. Moreover, the research is based on the notion that women emancipation practices decisively affect the community's identity and areas of action. After providing a theoretical overview and presenting relevant examples of the process of participatory heritage mapping, this paper analyzes the potential of community mapping methods using the abovementioned example. Additionally, it considers possibilities for interpreting community heritage that, until now, has not been widely represented within official heritage institutions.